2012
DOI: 10.1021/jo202265j
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Singlet Oxygen from Fragmentation of Monoactivated 1,1-Dihydroperoxides

Abstract: The first singlet excited state of molecular oxygen (1O2) is an important oxidant in chemistry, biology, and medicine. 1O2 is most often generated through photosensitized excitation of ground state oxygen. 1O2 can also be generated chemically through the decomposition of hydrogen peroxide and other peroxides. However, most of these “dark oxygenations” require water-rich media associated with short 1O2 lifetimes, and there is a need for oxygenations able to be conducted in organic solvents. We now report that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…In contrast to Pd II and Pt II complexes, Ln porphyrinates have been much less studied although some of them display oxygen‐sensitive phosphorescence with long lifetimes (up to 100 μs). In this work, the catalytic activity of Gd III complexes ( Gd‐1 – 4 ) was initially evaluated by photo‐oxygenation of diphenylisobenzofuran (DPBF), using UV/Vis spectroscopy to monitor the reaction process . As shown in Figure a, these Gd complexes can effectively lead to the decay of DPBF whereas Yb complexes are not reactive upon irradiation with white light (400–700 nm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to Pd II and Pt II complexes, Ln porphyrinates have been much less studied although some of them display oxygen‐sensitive phosphorescence with long lifetimes (up to 100 μs). In this work, the catalytic activity of Gd III complexes ( Gd‐1 – 4 ) was initially evaluated by photo‐oxygenation of diphenylisobenzofuran (DPBF), using UV/Vis spectroscopy to monitor the reaction process . As shown in Figure a, these Gd complexes can effectively lead to the decay of DPBF whereas Yb complexes are not reactive upon irradiation with white light (400–700 nm).…”
Section: Resultsmentioning
confidence: 99%
“…In this work, the catalytic activity of Gd III complexes (Gd-1-4)w as initially evaluated by photo-oxygenation of diphenylisobenzofuran (DPBF), using UV/Vis spectroscopy to monitort he reaction process. [30] As shown in Figure4a, these Gd complexes can effectively lead to the decay of DPBF whereas Yb complexes are not reactiveu pon irradiation with white light (400-700nm). Among Gd-1-4, Gd-4 displayed the highest reactivity when using either white (400-700 nm) or red (600-700nm) light irradiation, which is consistent with the order of 1 O 2 production (Gd-4 > Gd-3 > Gd-2 > Gd-1).…”
Section: Singletoxygen Related Photocatalysismentioning
confidence: 96%
“…Gem dihydroperoxide 57 may also be formed in an uncatalyzed reaction between H 2 O 2 and 1-hydroxyhydroperoxide 52 [ 80 , 81 ]. Hang et al [ 82 ] reported that some monosubstituted 1,1-dihydroperoxides undergo decomposition to produce singlet oxygen in high yield. A reaction of 57 with a gem diol may generate such monosubstituted 1,1-dihydroperoxide 58 as a precursor of singlet oxygen.…”
Section: Singlet Oxygen Formation By the Reaction Of Hydroperoxidmentioning
confidence: 99%
“…The substrates, easily generated through monoacylation of 1,1‐dihydroperoxides, undergo fragmentation in the presence of fluoride or alkoxide; the reaction can also be triggered by fluoride‐promoted desilylation of a trialkylsilylperoxide or by acylation or sulfonation of 1,1‐dihydroperoxides in the presence of excess base. A postulated mechanism involving an extremely low‐barrier Grob‐type fragmentation (Figure ) is supported by calculations and by the observation that the step associated with proton removal is rate limiting , …”
Section: Reactionsmentioning
confidence: 99%